Long‐term clearance of hepatitis C virus following interferon α‐2b or peginterferon α‐2b, alone or in combination with ribavirin. Issue 8 (3rd March 2013) - Manns, M. P.; Pockros, P. J.; Norkrans, G.; Smith, C. I.; Morgan, T. R.; Häussinger, D.; Shiffman, M. L.; Hadziyannis, S. J.; Schmidt, W. N.; Jacobson, I. M.; Bárcena, R.; Schiff, E. R.; et al.
Summary Sustained virologic response (SVR) is the standard measure for evaluating response to therapy in patients with chronic hepatitis C (CHC). The aim of this study was to prospectively assess the durability of SVR in the pivotal studies of peginterferon (PEG‐IFN) α‐2b or IFN α‐2b. We conducted two phase 3b long‐term follow‐up studies of patients previously treated for CHC in eight prospective randomized studies of IFN α‐2b and/or PEG‐IFN α‐2b. Patients who achieved SVR [undetectable hepatitis C virus (HCV) RNA 24 weeks after completion of treatment] were eligible for inclusion in these follow‐up studies. In total, 636 patients with SVR following treatment with IFN α‐2b and 366 with SVR following treatment with PEG‐IFN α‐2b were enrolled. Definite relapse (quantifiable serum HCV RNA with no subsequent undetectable HCV RNA) was reported in six patients treated with IFN α‐2b and three patients treated with PEG‐IFN α‐2b. Based on these relapses, the point estimate for the likelihood of maintaining response after 5 years was 99.2% [95% confidence interval (CI), 98.1–99.7%] for IFN α‐2b and 99.4% (95% CI, 97.7–99.9%) for PEG‐IFN α‐2b. Successful treatment of hepatitis C with PEG‐IFN α‐2b or IFN α‐2b leads to clinical cure of hepatitis C in the vast majority of cases.